Brazilians in Chile During the Military Dictatorship: Double Refuge 1973-1975 [Brasileños en Chile Durante la Dictadura Militar: Doble Refugio 1973-1975] - Norambuena-Carrasco, C; Palomera-Valenzuela, A (Universidade do Vale do Rio dos Sinos, 2018)
After the coup d’état of 1964 against the government of João Goulart in Brazil and the dictatorships that followed, Brazilians began to leave the country, and many of them sought refuge in other Latin American nations. This paper discusses the case of Brazilian citizens who, having acquired protection and refuge in Chile, had to move once again in 1973 because of the coup d’état of the Armed Forces and the subsequent dictatorial government of General Augusto Pinochet Ugarte, facing a new or double refuge. The review of primary sources focused on the safe-conducts issued by the Ministry of Foreign Affairs of Chile, which allows identify the number and condition of those who obtained the refugee status, as well as evidence of the importance of international and national organizations such as UNHCR, CIME, CONAR and FASIC in the protection of expatriates during the military dictatorship in Chile. © 2018 Universidade do Vale do Rio dos Sinos. All rights reserved.